Labour Markets and Demographic Change
296 p.
Keywords: This collection of research papers explores some of the salient issues relating to the impact of demographic change on the workings and outcomes of labour markets. A first chapter studies the direct impact of ageing on employment and unemployment. However, the age structure of the workforce also shapes productivity and the scope for innovation, issues which are taken up in turn. Furthermore, it is often argued that a decline in the size of the workforce may be offset by an increase in the workers’ skills and knowledge. The impact of demographic developments such as ageing and migration on the accumulation and transfer of human capital is, therefore, studied by a further set of contributions. The volume is rounded off with analyses relating to the supply of labour by women and by older workers. The authors ask, for instance, whether (female) labour migration as well as changes in retirement patterns and policies may counterbalance the expected workforce shrinking.